Cicero and Augustine: contrasting figures to think politics (2005)
This text reflects on the thoughts of Cicero and Agustín de Hipona, as two antagonistic models when it comes to thinking about political essentiality. While in the case of the Roman jurist, the notions of Justice and sociability are emphasized as central